A multi-level analysis of the direct and joint effects of gender and mode of disposition on sentencing in federal courts - Holmes, Bryan M. (Criminal justice studies, 2020)
The current study examines the influence of defendant sex, mode of disposition, and sex-by-mode of disposition grouping on incarceration and sentence length decisions. In addition, this study examines contextual effects on the trial penalty for males and females. Generally, findings suggest that females receive more lenient sentences, those convicted via plea receive more lenient sentences, and males convicted via trial receive harsher sentences than all other sex-by-mode of disposition grouping. Analysis of cross-level interactions signify that districts which sentenced higher average offense levels had smaller trial penalties at the incarceration decision and larger trial penalties at the sentence length decision for both males and females. Meanwhile, no detectable influence of caseload size on the effect of sex, mode of disposition, and their intersections at either sentencing point was found. Implications for the study findings are discussed and future avenues of research are recommended.